Kissing Christians: ritual and community in the late ancient church - Penn, Michael Philip (Divinations, 2005)
Kissing basics -- The kiss that binds : Christian communities and group cohesion -- Difference and distinction : the exclusive kiss -- Boundary violations : purity, promiscuity, and betrayal -- Conclusion